ECOLOGICAL RESTORATION OF DISTURBED LOW-ARCTIC UPLAND HEATH USING LOCALLY SOURCED, TRANSPLANTED VEGETATIVE TURFS - Hnatowich, Ian (2022)
Arctic environments have undergone ecological disturbances from industrial resource extraction for decades, yet knowledge of arctic plant-soil systems and effective means of ecological restoration is still largely unknown and understudied. To gain a better understanding of restoring arctic plant communities following mining disturbance, we examined whole turf transplants and shredded tundra material in maintaining vegetative community characteristics and soil nutrient concentrations two years post-transplantation onto disused gravel quarries. Community characteristics, and recovery of turf harvesting locations were determined through quadrat assessments, and soil nutrients were assessed through ion chromatography of soil samples. Additional turfs were harvested and transported to the University of Saskatchewan to investigate the effects of turf-adjacent fertilization on turf and substrate community characteristics, above and belowground biomass, and distance of vegetation expanding from the turf. Quadrat assessments were conducted to investigate community characteristics, and above and belowground biomass was harvested at specific distance increments from the turf. DNA metagenomics was used to identify the species responsible for expansion Overall, we found turf transplants were capable of surviving transplantation and extreme environmental conditions and transferred native species and vegetative cover to disturbed sites. The application of shredded tundra material may be effective at re-instating non-vascular communities over a large area, although requires greater protection from wind and water erosion. We found belowground expansion far exceeded aboveground and that graminoids were primarily responsible for this expansion. Fertilization of turf’s surroundings increases belowground biomass and the development of biological soil crusts on adjacent substrates, without impacting the development of vegetation within the turfs. We recommend that restoration practitioners seek to transplant forb and ...